Uji Efektivitas Ekstrak Daun Urang Aring sebagai Insektisida Alami terhadap Mortalitas Kutu Kepala (Pediculus Humanus Capitis) - Citra Ayu Prameswari; Izza Ratna Kumala (Jurnal Medika Husada, 2024)
Pediculosis capitis is a scalp disease caused by infection of lice-the species Pediculus humanus capitis, that is very common in primery school aged-children. Community efforts to overcome head lice include using chemical insecticides, but excessive use can have negative impacts. Efforts to reduce negative impacts include the use of biorational pesticides made from natural ingredients. urang aring leaves are also one of the natural ingredients that can be used. The leaves contain several compounds that can be used as insecticides. This study aims to determine the effectiveness of urang aring leaf extract on the mortality of Pediculus humanus capitis. The type of research conducted was experimental about the effectiveness testing of urang aring leaf various concentrations extract on Pediculus humanus capitis mortality. 125 adult Pediculus humanus capitis were taken by using Random sampling method. The results were a 5% concentration had an average mortality of 2.6 (53.33%) or about 2-3 heads. The 25% concentration averaged 3.5 (70%) deaths or about 3-4 heads. Concentration 50% average mortality 4.5 (90%) or about 4-5. Concentration 100% average mortality 5 (100%) or all dead. Urang aring extract in this rsearch is effective in killing Pediculus humanus capitis and the most optimal concentration is 100% concentration.